Global Renewable-Based Electrification Pathways and Its Long-Term Scenario Analysis - Bowen HONG; Asami MIKETA; Dolf GIELEN; Daniel RUSSO; Luis JANEIRO; Francisco BOSHELL; Nicholas WAGNER; Emanuele TAIBI (Zhongguo dianli)
To meet the deep-decarbonisation need of a clean energy transition, the paper is dedicated to working out a blueprint of a renewable-based electrification future, in almost every aspects from its pathways to the potentials and benefits. Also the challenges it faces in industry, transport, and building sectors are analyzed and recommendations are proposed to cope with them in policy, technology, and market aspects. According to the results, it is not only technically feasible but also economically and socially beneficial to implement such a renewable-based electrification.